HIV Associated Neurodegenerative Disorders: A New Perspective on the Role of Lipid Rafts in Gp120-Mediated Neurotoxicity - Smith, Lisa K.; Kuhn, Thomas B.; Chen, Jack; Bamburg, James R. (Current HIV Research, 2018)
The implementation of combination antiretroviral therapy (cART) as the primary means of treatment for HIV infection has achieved a dramatic decline in deaths attributed to AIDS and the reduced incidence of severe forms of HIV-associated neurocognitive disorders (HAND) in infected individuals. Despite these advances, milder forms of HAND persist and prevalence of these forms of neurocognitive impairment are rising with the aging population of HIV infected individuals. HIV enters the CNS early in the pathophysiology establishing persistent infection in resident macrophages and glial cells. These infected cells, in turn, secrete neurotoxic viral proteins, inflammatory cytokines, and small metabolites thought to contribute to neurodegenerative processes. The viral envelope protein gp120 has been identified as a potent neurotoxin affecting neurodegeneration via indirect and direct mechanisms involving interactions with chemokine co-receptors CCR5 and CXCR4. This short review focuses on gp120 neurotropism and associated mechanisms of neurotoxicity linked to chemokine receptors CCR5 and CXCR4 with a new perspective on plasma membrane lipid rafts as an active participant in gp120-mediated neurodegeneration underlying HIV induced CNS pathology.
Keywords: cholesterol